Ethnopharmacological and Ethnobotanical study of Medicinal plants in the Central High Atlas, Morocco الدراسة الإيثنوفرمكولوجية والإ ثنوبولوجیة للنباتات الطبية في الأطلس المتوسط الكبير للمغرب. - Belhaj, Souad; Dahmani, Jamila; Belahbib, Nadia; Zidane, Lahcen (Ethnobotany Research and Applications, 2020)
Background: This ethnobotanical and ethnopharmacological study was conducted in the High Atlas Central of Morocco. Its aim is to promote the use of medicinal plants through the realisation of an inventory of these plants and their therapeutic uses in this region. Methods: The ethnopharmacological surveys conducted in the field from 2015 to 2017 have allowed filling 1192 questionnaires. Information was collected by an ethnobotanical and a floristic survey with using open-ended and semi-structured interviews. Data were analyzed using ANOVA and Student’s t test; Quantitative ethnobotanical indices such as Fidelity Level (FL), Relative Citation Frequency (RCF) Frequency (F), and Family Importance Value (FIV) were also used to compare data. The medicinal plants were collected, identified and kept at the Biodiversity and Natural Resources Laboratory, Ibn Tofail University, Kenitra. Results: The study identified a total of 248 medicinal plants used by the local population. They belong to 70 families from which the leading family was Asteraceae, represented by 30 species. Most of these species are used to treat gastrointestinal diseases such as Thymus broussonetii Boiss, Ceratonia siliqua L. and diabetic diseases such as Anthemis nobilis L., Euphorbia resinifera Berg. These diseases are mainly cured using leaves of the plants cited. The predominant preparation method is decoction. Conclusions: This study showed that indigenous people in the High Atlas Central use the plants recorded for the treatment of various diseases. This wealth of plants for therapeutic uses is accompanied by knowledge and practices in phytotherapy acquired by the inhabitants of the High Atlas Central over the centuries. This study keeps a transcribed trace of phytotherapy practices. The achieved results are a precious source of ethnomedicinal knowledge that allows the shifting of the researches towards phytochemistry and pharmacology. Key words: Ethnomedicinal, Therapeutic uses, Medicinal plants, Biodiversity. ملخص: المقدمة: أجريت هذه الدراسة الإيثنوفرمكولوجية والإ ثنوبولوجیة للنباتات الطبية في الأطلس المتوسط الكبيرللمغرب,والتي تهدف إلى تثمين هذه النباتات وذلك من خلال جردها وتحديد استخداماتها العلاجية من قبل السكان المحليين لهذه المنطقة. الأساليب: مكنت هذه الدراسة من ملء 1192 استمارة معلوماتية تظم دراسات استقصائية إثنوبولوجية ونباتية, أجريت في منطقة البحث, بين سنتي 2015 و 2017, وذلك بإجراء مقابلات مفتوحة وشبه منظمة ,وقد تم تحليل ومقارنة البيانات باستخدام (اختبار أنوفا واختبار ط ، حيث يكون الاختبار مهمًا عندما تكون القيمة ـ بــ ـ (ب ≤ 0.05)) و باستخدام مؤشرات نباتية إثنية كمية مثل قيمة استخدام الأسرة (ق.ا.أ) ، والتكرار النسبي للاستشهاد (ت.ن.ا)، ومستوى الإخلاص (م.إ). ليتم جمع النباتات الطبية ,تسميتها وحفظها في مختبر الموارد الطبيعية والتنوع البيولوجي ، جامعة ابن طفيل ، القنيطرة. النتائج: مكنت هذه الدراسة من تحديد ما مجموعه 248 نوعا من النباتات الطبيةالمستخدمة من طرف السكان المحلييين. حيت تنتمي هذه النباتات إلى 70 عائلة نباتية ,أكثرها تمثيلًا هي فصيلة النجميات ب 30 نوعًا,و يتم استخدام معظم هذه الأنواع لعلاج أمراض الجهاز الهضمي ,مثل تيميس بروسونتي و سيراطونيا سيليكا ,وأمراض السكري ,مثل أنتيميس نوبليس و أوفوربيا غيسينيفورا.ويعتبرالنقيع أكثرالطرق استعمالا لإعداد الوصفات, بينما تعد الأوراق الجزء الرئيسي المستخدم في العلاجات. الاستنتاجات: أظهرت هذه الدراسة أن السكان المحليين في الأطلس المتوسط الكبيريستخدمون 248 نوعًا نباتيًا لعلاج مختلف الأمراض, هذه الثروة المعرفية مرتبطة بممارسات العلاج بالنباتات التي اكتسبها سكان هذه المناطق على مر القرون. و تعتبر النتائج المحصل عليها بمثابة مصدر غني من المعلومات, قد يمكن من معرفة النباتات الطبية وتوجيه الدراسات الكيميائية النباتية والدوائية. الكلمات المفاتيح: الطب الإثني ، الاستخدامات العلاجية ، النباتات الطبية ، التنوع البيولوجي ؛